Learning Video Making Training Multimedia Based Using Powtoon For Teachers Of State 12 Junior High School, Sungai Raya, Regency. Kuburaya - Sujatmiko, Wandi (Edumedia Solution, 2023)
Education is a real effort to facilitate other individuals in achieving independence and mental maturity so that they can survive in the competition of life. In educational activities, students are targets (objects) and at the same time as educational subjects. In Tilaar's perspective, multicultural education originated from the development of the idea of